Health Literacy Related to Covid-19 on Senior High School and Vocational High School Students in Indonesia: A Descriptive Study: Health Literacy Related to Covid-19 High School and Vocational High School Students in Ponorogo District in 2021 - Anisa Emilia Putri; Mujiyono (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
ABSTRACT The presence of the COVID-19 pandemic is also accompanied by the birth of an infodemic whose spread can even be faster than the spread of the virus itself. Rapid dissemination of information makes the information circulated out of control. Health literacy is a competency that needs to be possessed to improve quality health and is expected to suppress the troubling infodemic. The indicator in seeing the quality of a person's health literacy is by looking at how access, understanding, assessment, and also the application of health information related to covid-19 is, therefore this study has the aim of knowing health literacy related to covid-19 high school and vocational high school students in Ponorogo District. This type of research is descriptive with a quantitative survey approach, the population in this study was 8102 students which was then carried out by sampling so that a sample of 367 students was obtained. This research was conducted in 19 SMA and SMK in Ponorogo District. The sampling technique used is purposive sampling. The research data that has been obtained is then analyzed using frequency. The results showed that students' health literacy got quite good results, 92.9% of the total respondents had sufficient health literacy, some of them namely 6.8% of respondents had problematic health literacy results, and the remaining 0.3% had inadequate health literacy. The conclusion of this study is that the health literacy of high school and vocational students in Ponorogo District is good. The suggestion from this research is that it is necessary to increase individual abilities in terms of access, understanding, assessment and also the application of health information about COVID-19 so that it can improve the quality of individual literacy which will have a good impact on improving the quality and welfare of individuals in the health sector.